Patch
Patent Information
- Application Number
- JP2023133000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-28
AI Technical Summary
【0008】 本発明の貼付材は、水への浸漬後においても自背面粘着力が高いため、該貼付材を指などに周回して貼付し、水仕事など水中での作業を行なった後においても、貼付材の重ね貼りの部分からの剥がれが少ない、付着性に優れたものとすることができる。 さらに本発明の貼付材は、支持体である編布地が低伸長時における適度な引張荷重と良好な透湿度とを有するため、該貼付材を関節部に貼付した場合においても、関節の動きを大きく妨げることなく、また汗等による蒸れが生じにくい、貼り心地の良い貼付材とすることができる。
Smart Images

Figure 2025027840000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive patch, particularly an adhesive patch that is easy to use when applied to affected areas such as hands, fingertips, knees, and other parts of the body that are highly curved or bent, particularly an adhesive patch known as a first aid bandage. [Background technology]
[0002] For first aid bandages (adhesive patches) that are applied to protect affected areas such as cuts and scrapes, a product has been proposed that uses a polyurethane nonwoven fabric as the support (base material), which has good conformability to the movement of the skin on the wrist, knee, etc. and is also highly breathable. Also, for users who do long hours of wet work in cooking or welfare, or who perform hard work or tasks indoors or outdoors, patches have been proposed that use knitted fabric as a support, which adheres firmly to the skin, does not come loose during use, and has sufficient fixing performance even in areas that are highly flexible and stretchable, such as joints. For example, a skin application tape using a warp knitted fabric woven into a power net structure with inelastic yarns and elastic yarns (Patent Document 1) and a patch using a warp knitted fabric with polyester filaments and polyurethane elastic filaments (Patent Document 2) have been proposed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2011-32625 A [Patent Document 2] JP 2011-67615 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the examples of Patent Document 1, the elasticity and breathability of the backing (fabric for the tape) of the skin adhesive tape itself are evaluated, and the fixation, conformability, stuffiness, rolling-up, etc. of the skin adhesive tape are also examined. However, there is no discussion or examination at all of the adhesiveness of the tape after the skin adhesive tape is applied to a finger or the like and used for water work. Furthermore, although the patch in Patent Document 2 is evaluated for its adhesion to the skin after wet work and the state of attachment of overlapping parts of the patch, it is difficult to prevent peeling of the overlapping parts of the patch after wet work, etc.
[0005] The object of the present invention is to provide a patch which, when the adhesive layer of the patch is attached to the surface of the support of the patch (for example, the patch is attached by wrapping it around a finger or the like), has high adhesive strength on its back side (adhesive strength when multiple patches are attached), and is not likely to peel off, even after being immersed in water for a predetermined period of time; and to provide a patch which causes little sweating on the skin when attached and which can follow the movement of joints. [Means for solving the problem]
[0006] That is, the present invention is directed to the following patches. [1] A patch having a backing and an adhesive layer provided on one side of the backing, wherein the adhesive layer of the patch is attached to the surface of the backing of the patch, the patch is immersed in 45°C water for 30 minutes, and in a post-immersion backing adhesive strength test in which the adhesive strength after removal from the water is measured, the post-immersion backing adhesive strength (longitudinal direction) is 2.0 N / 15 mm or more.
[0007] Furthermore, the present invention provides the following embodiments. [2] The support is a knitted fabric composed of polyester inelastic yarn and polyurethane elastic yarn, and the knitted fabric has a course density of more than 210 threads / inch and not more than 270 threads / inch and a thickness of The patch according to [1], which has a thickness of 0.25 mm to 0.40 mm. [3] The knitted fabric has a welt density of 25 threads / inch to 50 threads / inch, a polyester inelastic yarn fineness of 30 to 100 dtex, a polyurethane elastic yarn fineness of 100 to 300 dtex, and a basis weight of 80 g / m 2 ~150g / m 2 The patch described in [2]. [4] The patch according to [1], wherein the patch has a 20% tensile load in the longitudinal direction of 2.5 N / 20 mm to 4.5 N / 20 mm. [5] The adhesive has a moisture permeability of 3,000 g / m 2 -The patch described in [1], which has a duration of 24 hours or more. [6] The patch described in [1], wherein the adhesive layer contains a foamed acrylic adhesive. [7] The adhesive material described in [1] that does not leave any glue residue. Effect of the Invention
[0008] The patch of the present invention has high adhesive strength on its back side even after immersion in water, and therefore when the patch is wrapped around a finger or the like and applied, even after performing wet work or other underwater tasks, the patch has excellent adhesion with little peeling from the overlapping areas. Furthermore, the patch of the present invention, because the knitted fabric support has an appropriate tensile load at low elongation and good moisture permeability, even when the patch is applied to a joint, it does not significantly impede joint movement and is less likely to become stuffy due to sweat, etc., making it a comfortable patch to apply. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a cross-sectional view of a first aid adhesive bandage, which is one embodiment of the patch of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Adhesive material] The present invention is directed to an adhesive material having a backing and an adhesive layer provided on one side of the backing, and the adhesive material is also called a first aid adhesive bandage. One embodiment of the patch of the present invention when it is a first aid adhesive bandage is shown in Figure 1. As shown in Figure 1, the first aid adhesive bandage 1 is formed by providing an adhesive layer 3 on one side of a support 2, placing a patch 4 in the approximate center of the adhesive layer 3, and layering a release material 5 (5a, 5b) so as to cover the adhesive layer 3 and the patch 4.
[0011] <Self-back adhesive strength after immersion> The patch of the present invention is characterized in that its backside adhesive strength after immersion in 45° C. water for 30 minutes (backside adhesive strength after immersion) (longitudinal direction) is 2.0 N / 15 mm or more. In the present invention, the adhesive strength of the back surface refers to the peel strength when the adhesive layer of the patch is attached to the surface of the support of the patch and then peeled off in a direction of 180°. The patch of the present invention has its own backside adhesive strength after immersion as described above, and therefore can provide a patch that has good adhesion and does not peel off in the overlapping portion even after the patch is wrapped around a finger or the like underwater and used for work such as washing with water.
[0012] As an example of a specific test procedure for the self-adhesive strength after immersion, the target adhesive material (without a pad) is cut into two pieces of 100 mm (longitudinal direction) x 15 mm (lateral direction) to prepare test pieces, one test piece is attached to a Bakelite board, and the other test piece is placed on top of the first one, and then pressed twice back and forth at 600 mm / min with a 1 kg roller. The pressed sample is immersed in water at 45°C for 30 minutes. After 30 minutes, the sample is removed from the water and the moisture on the sample surface is lightly wiped off, and then a 180° peel test is performed using an Instron tensile tester at a speed of 300±30 mm / min from the longitudinal direction, and the 180° peel strength (N) is measured (unit: N / 15 mm). The upper limit of the adhesive strength on the back surface of the patch of the present invention is not particularly limited, but if it is too high, the patch will be difficult to remove when replacing it, and therefore the upper limit can be, for example, 10.0 N / 15 mm or less, 8.0 N / 15 mm or less, or 6.0 N / 15 mm or less.
[0013] <20% tensile load> The patch of the present invention (backing material + adhesive layer) can have a 20% tensile load of, for example, 2.5 N / 20 mm to 4.5 N / 20 mm. By setting the 20% tensile load within the above range, it is possible to obtain a patch that provides an appropriate feeling of tightness and is less likely to become loose when applied. In the present invention, the 20% tensile load is measured according to JIS L 1096, and is the load (stress, unit N / 20 mm) when stretched 20% in the longitudinal direction (the longitudinal direction of the support (preferably the mesh fabric described below)) under conditions of a gripping distance of 100 mm and a moving speed of 300 mm / min. Note that the value of the 20% tensile load is the value for the patch (support + adhesive layer), but it has been confirmed that the value does not change when only the support is used.
[0014] <Moisture permeability> The patch of the present invention (backing material (preferably the knitted fabric described below) + adhesive layer) has a moisture permeability of 3,000 g / m2 as measured according to JIS Z 0208 at 40°C and 90% RH. 2 The moisture permeability is preferably, for example, 4,000 g / m 2 24h or more, or 5,000g / m 2 24h and 6,000g / m 2 24h or more, e.g. 7,000g / m 2 -24h or more. There is no upper limit for moisture permeability, but it is usually 30,000g / m 2 Less than 24 hours. The moisture permeability of the patch according to the present invention is 3,000 g / m 2 By leaving it on for 24 hours or more, it is possible to reduce the amount of moisture that builds up when the patch is applied to the skin, and to reduce the risk of skin irritation or itching while the patch is in place.
[0015] <Support> As the backing material used in the patch of the present invention, a knitted fabric composed of non-elastic polyester yarn and elastic polyurethane yarn can be used. The knitted fabric may be a warp knitted fabric selected from tricot knit, raschel knit, and millennium knit.
[0016] The ratio of polyester non-elastic yarn to polyurethane elastic yarn in the knitted fabric is not particularly limited, but for example, based on the total mass of the knitted fabric, the polyester non-elastic yarn:polyurethane elastic yarn = 95-70 mass%:5-30 mass%, or 90-75 mass%:10-25 mass%, 90-80 mass%, or 10-20 mass%. By setting the ratio of polyester inelastic yarn to polyurethane elastic yarn within the above range, it is possible to obtain a knitted fabric and patch that achieves a good balance between elasticity and fixation (tightening effect) to the affected area and is less prone to curling of the fabric. In the knitted fabric, a blend of polyester inelastic yarn and polyurethane elastic yarn may be used, or polyester inelastic yarn and polyurethane elastic yarn may be interwoven.
[0017] In the knitted fabric, the fineness of the polyester non-elastic yarn can be, for example, 30 to 100 dtex, 40 to 80 dtex, or 40 to 70 dtex. By setting the fiber of the polyester non-elastic yarn within the above range, a knitted fabric having an appropriate thickness can be obtained, and a knitted fabric and patch that are well balanced with the elastic yarn and have appropriate elasticity can be obtained. The fineness of the polyurethane elastic yarn can be, for example, 100 to 300 dtex, 120 to 200 dtex, or 130 to 180 dtex. By setting the fineness of the polyurethane elastic yarn within the above range, it is possible to obtain a knitted fabric and a patch having an appropriate fixing function (action of restraining the affected area) and a feeling of tightness.
[0018] The knitted fabric may have a course density of more than 210 threads / inch and not more than 270 threads / inch, and a well density of 25 threads / inch to 50 threads / inch. By setting the density of the knitted fabric within the above ranges, it is possible to obtain a knitted fabric and patch that can adequately restrain the affected area and has adequate elasticity to follow the movement of the joint. In particular, by setting the course density to more than 210 fibers / inch and not exceeding 270 fibers / inch, the manufactured adhesive material can have the desired post-immersion backside adhesive strength of 2.0 N / 15 mm or more. If the course density is less than 210 fibers / inch, the post-immersion backside adhesive strength falls below 2.0 N / 15 mm, resulting in poor adhesion when actually layered. For example, Patent Document 1 points out that if the course density of the knitted fabric supporting body exceeds 210 threads / inch, the knitted fabric becomes thick and hard, hindering movement of the joints and reducing breathability and making the fabric prone to becoming stuffy. In the present invention, even if the course density of the knitted fabric exceeds 210 threads / inch, the thickness of the knitted fabric and the fineness of the inelastic yarn and elastic yarn constituting the knitted fabric are appropriately selected to achieve a knitted fabric that conforms to the affected area and is breathable.
[0019] The thickness of the knitted fabric is, for example, 0.25 mm to 0.40 mm, and the weight per unit area is, for example, 80 g / m 2 ~150g / m 2 By setting the thickness and basis weight within the above ranges, it is possible to obtain a knitted fabric and patch that can adequately restrain the affected area, has appropriate elasticity, can follow the movement of the joint, and is less likely to become stuffy.
[0020] The course density and thickness of the mesh fabric are preferably within the above numerical ranges, and for example, the course density can be 220 threads / inch to 260 threads / inch, and the thickness can be 0.3 mm to 0.4 mm, etc. If the thickness is 0.40 mm or more, when used as an adhesive material, the overlapping parts tend to get caught and be easily subjected to load, and there is a risk that the adhesive strength may be impaired.
[0021] The shape of the support (knitted fabric) is not particularly limited, and various shapes can be selected according to the application location, such as a rectangle (square, rectangle, etc.), quadrangle (trapezoid, rhombus, etc.), polygon, circle, ellipse, semicircle, triangle, crescent, and combinations of these. In the case of a shape with corners, such as a rectangle, quadrangle, or polygon, the corners can be rounded to prevent the adhesive from peeling off from the application location (when the adhesive is applied to the entire surface of the support). When the adhesive material according to the present invention is in the form of the above-mentioned first aid adhesive bandage, it may have, for example, a substantially square or substantially rectangular shape based on a square or rectangle.
[0022] <Adhesive layer> The adhesive layer formed on one side of the support can be formed using other adhesives such as (natural / synthetic) rubber-based adhesives, acrylic-based adhesives, urethane-based adhesives, silicone adhesives, polyvinyl alcohol-based adhesives, polyamide-based adhesives, etc. These adhesives may be used alone or in combination of two or more. Among them, acrylic-based adhesives can be used from the viewpoints of sufficient adhesion to the skin surface, low irritation to the skin, and high moisture permeability.
[0023] Examples of the acrylic adhesive include homopolymers of alkyl ester monomers of (meth)acrylic acid having about 4 to 12 carbon atoms, such as butyl acrylate, 2-ethylhexyl acrylate, and isononyl acrylate, or copolymers of these monomers, and further, adhesives containing copolymers of the alkyl ester monomers of (meth)acrylic acid and other monomers copolymerizable with the alkyl ester monomers of (meth)acrylic acid, such as (meth)acrylic acid, hydroxyalkyl esters of (meth)acrylic acid, vinyl acetate, styrene, vinylpyrrolidone, (meth)acrylamide, and alkoxyalkyl (meth)acrylates. Examples of such agents include: The acrylic pressure-sensitive adhesive may be a solvent-type adhesive obtained by polymerizing the monomer in an organic solvent such as toluene, hexane, ethyl acetate, or the like under a nitrogen atmosphere using a peroxide such as benzoyl peroxide as an initiator, or may be an emulsion-type adhesive obtained by emulsifying and dispersing the monomer in water with an emulsifier, followed by polymerization. In addition to the acrylic adhesives containing tackifier resins such as rosin resins, terpene resins and terpene phenol resins, and crosslinkers such as polyfunctional epoxy resins, the adhesive layer may contain, as optional components, additives that may normally be blended into adhesive layers, such as tackifiers, crosslinkers, softeners (plasticizers), pH adjusters, antioxidants (antioxidants, preservatives), fillers, UV absorbers, colorants and fragrances.
[0024] In addition, it is more preferable to use a foamed adhesive, since it can improve the breathability and cushioning properties. The foaming of the adhesive can be carried out by a conventional method, such as a method using a foaming agent as described below, or a method utilizing the vaporization effect that occurs when an aqueous solution or an organic solvent is heated.
[0025] In the patch of the present invention, the adhesive layer is formed so as to cover the surface of one side of the knitted fabric as the support, preferably over the entire surface, but may be formed partially (patterned) on the one side as long as the effect of the present invention is not impaired. When the adhesive layer is formed partially, any shape such as a lattice, net, granular, arabesque pattern, etc. can be selected. By forming the adhesive layer partially, the breathability and moisture permeability of the patch can be further improved, and the irritation when peeled off from the skin can be adjusted (reduced). The pressure-sensitive adhesive layer may be a single pressure-sensitive adhesive layer or a laminate of multiple pressure-sensitive adhesive layers. When the pressure-sensitive adhesive layer is a laminate of multiple pressure-sensitive adhesive layers, different types of pressure-sensitive adhesive layers may be laminated.
[0026] The thickness of the pressure-sensitive adhesive layer can usually be 10 μm to 200 μm, for example, 20 μm to 100 μm.
[0027] <Backing material> As described above, the patch of the present invention can be in the form of a first aid bandage, for example, in the form of a patch provided with a patch. The patch is made of a material that can protect the affected area (wound) and absorb body fluids (exudates) from the affected area, and can usually be made of absorbent materials such as gauze, nonwoven fabric, compressed fiber, hydrocolloid, or laminates of these. Depending on the area where the patch is used, the upper surface of the material can be thin-filmed (e.g., mesh-like film) with polyethylene or other plastics to prevent body fluids from coming out of the affected area from adhering to the affected area. Furthermore, the patch can hold disinfectants, therapeutic drugs and other medicines, if necessary.
[0028] The shape of the patch is not particularly limited, and various shapes can be selected according to the area to which it is to be applied, such as a rectangle (square, rectangle, etc.), quadrilateral (trapezoid, rhombus, etc.), polygon, circle, ellipse, semicircle, triangle, crescent, or a combination of these. The thickness of the application material can be appropriately set, for example, to 0.5 to 2.0 mm, or 0.7 to 1.5 mm.
[0029] <Removal material> The release material is provided for the purpose of protecting the adhesive layer and the patch until immediately before the patch is used, and embodiments comprising such a release material can also be included in the patch of the present invention. The release material can be any of those commonly used in the technical fields of adhesive tapes and patches. For example, paper substrates such as fine paper and glassine paper, plastic films such as polyester (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), release-processed paper coated with a release agent having release properties such as silicone resin or fluororesin, laminated paper in which these films are laminated, and laminated release-processed paper in which the laminated paper is coated with a release agent can be used. The thickness of the release material is not particularly limited, but is usually in the range of 10 μm to 1 mm, for example, 20 μm to 500 μm, and preferably 40 μm to 200 μm. The weight per unit area is, for example, 50 to 150 g / m 2 Or 60~100g / m 2 It can be about that. The amount of release agent applied during the peeling process is usually 0.1 to 10 g / m 2 It can be about that. The shape of the release material can be square, rectangular, circular, etc., and can be rounded if desired. Its size can be the same as or slightly larger than the size of the support in the patch. The release material can be composed of one sheet or multiple divided sheets, and the cuts can be straight, wavy, or perforated, or the release materials can be partially overlapped with each other.
[0030] The patch of the present invention can be manufactured according to the manufacturing method of conventional patches and bandages.For example, first, an adhesive is applied to one side of the support to form an adhesive layer, and the patch is configured.Furthermore, a patch is placed on the adhesive layer, and a release material is laminated so as to cover the adhesive layer and the patch, thereby manufacturing a patch in the form of a first aid bandage. Specifically, for example, a solution or emulsion of an adhesive is applied onto a process paper coated with a silicone-based release agent or the like to form an adhesive layer, and then the adhesive layer and a support are laminated to produce an adhesive tape-like patch. The process paper is a general term for paper or film used during the manufacturing process that does not remain in the product, and the films and papers exemplified in the above-mentioned <release material> can be used here. If desired, after the adhesive is applied, the adhesive layer may be foamed to form a foamed adhesive layer having breathability. The breathable foamed pressure-sensitive adhesive layer (the pressure-sensitive adhesive layer containing a foamed pressure-sensitive adhesive) can be produced, for example, by the following methods 1) to 3). The pressure-sensitive adhesive layer having a large number of fine pores therein can be formed by the methods 1) to 3), but is not limited to these examples. 1) A method using a foaming treatment in which an adhesive (such as an adhesive solution diluted with an organic solvent, or an adhesive in an aqueous emulsion state) or an adhesive mixed with a physical foaming agent such as air, nitrogen gas, or carbon dioxide gas or a decomposition-type chemical foaming agent as required is applied to a process paper, or the adhesive is applied to a process paper that has been previously coated or sprayed with an aqueous solution or organic solvent; then, heating is performed to utilize the foaming or vaporization action; 2) A method in which a mist of water is applied or sprayed onto the wet surface of the applied pressure-sensitive adhesive, and then the applied pressure-sensitive adhesive is heated to 110 to 150°C, preferably 120 to 140°C, for usually 2 to 60 minutes, preferably 3 to 50 minutes, more preferably 5 to 40 minutes, to form fine pores; 3) A method in which the adhesive is discharged onto release paper in the form of threads or fibers. From the viewpoint of forming fine and uniform pores, 1) the method of obtaining a pressure-sensitive adhesive layer by foaming treatment is more preferable, and 2) the method of applying or spraying water is a simple method.
[0031] Next, the process paper of the adhesive tape-like patch is peeled off to expose the adhesive layer, and a patch cut to an appropriate size is placed on the adhesive layer in a predetermined position (for example, a position that will be approximately the center of the adhesive bandage when it is made into an adhesive bandage). Usually, a release material is further placed so as to cover the adhesive layer and the patch, and then the release material is cut into a predetermined shape to form a laminate of support / adhesive layer / patch / release material. It is possible to obtain a patch (first aid adhesive bandage) having the above structure. The produced patch (first aid bandage) is usually packed in a wrapping paper made of paper, plastic film, or a composite material thereof at room temperature in a later process to produce a finished product. At this time, sterilization may be performed as necessary. EXAMPLES
[0032] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0033] [Example 1] The patch (first aid adhesive bandage) shown in FIG. 1 was produced by the following procedure. The fabric is made of 85% polyester inelastic yarn of 44 dtex and 15% polyurethane elastic yarn of 156 dtex, with a well density of 36 threads / inch, a course density of 228 threads / inch, and a thickness of 0.30 mm (basis weight 112 g / m 2 ) was used as the knitted fabric of Example 1 (support 2). An adhesive [acrylic adhesive (a solution of an acrylic copolymer obtained by copolymerizing a monomer mixture consisting of 2-ethylhexyl acrylate / vinyl acetate / acrylic acid = 85 / 11 / 4 (mass ratio) was reacted with 20 parts by mass of a tackifier resin (YS Polystar T100, terpene phenol resin, manufactured by Yasuhara Chemical Co., Ltd., solid content concentration 26.88 mass%) and 0.04 parts by mass of a multifunctional epoxy crosslinking agent (Tetrad X, manufactured by Mitsubishi Gas Chemical Co., Ltd., solid content concentration 2.86 mass%) per 100 parts by mass of the acrylic copolymer] was applied at a coating amount of 40 g / m after drying. 2 The adhesive layer 3 was formed by applying the adhesive to one surface of the knitted fabric (support 2) of Example 1 so as to become This was cut into a belt-like shape with a length of 70 mm and a width of 21 mm, both ends of which were arched, and a pad (patch material 4) of 22 mm length and 13 mm width, made of rayon nonwoven fabric covered with a polyethylene net-like film, was placed in the center of the adhesive layer 3, which was then covered with a two-piece release material 5 (5a, 5b) (silicone-treated polylaminated wood-free paper), to produce the patch 1 (first aid bandage) of Example 1. The patch (first aid bandage) with the patch was used for the practical test described below, and a patch (support + adhesive layer + release material) without the patch was separately produced and cut to a specified size to be used for the tensile test described below, the measurement of moisture permeability, and the measurement of the adhesive strength on the back side when immersed. In the following description, the example numbers of the knitted fabrics will also be treated as example numbers of the adhesive materials and example numbers for the evaluation of each test.
[0034] [Examples 2 to 4] The patches of Examples 2 to 4 were obtained in the same manner as in Example 1, except that a knitted fabric (support) with a well density, course density and thickness as shown in Table 1 was used as the support for Examples 2 to 4. [Comparative Example 1] The patch of Comparative Example 1 was obtained in the same manner as in Example 1, except that a knitted fabric (support) having the ratio of polyester inelastic yarn and polyurethane elastic yarn, well density, course density and thickness as shown in Table 1 was used as the support of Comparative Example 1. [Comparative Example 2] The patch of Comparative Example 2 was obtained in the same manner as in Example 1, except that the knitted fabric of Comparative Example 2 was a warp-knitted fabric using 86% by mass of 60 dtex polyester inelastic yarn and 14% by mass of 216 dtex polyurethane elastic yarn, with a well density of 40 threads / inch, a course density of 207 threads / inch, and a thickness of 0.38 mm.
[0035] For the patches of Examples 1 to 4 and Comparative Examples 1 and 2, various evaluation tests were carried out according to the following procedures.
[0036] [Self-back adhesive strength after immersion] According to the 180 degree peeling method specified in JIS Z 0237, the adhesive strength of the patch itself was measured after immersion in water for a specified period of time. Specifically, from a sample of the adhesive material (original roll before punching (backing material + adhesive layer + release material, but no pad)) produced in each example, two test pieces were cut into strips measuring 100 mm in length and 15 mm in width, and designated as test pieces 1 and 2. Test piece 1 was attached to a Bakelite plate, and the other test piece 2 was then layered and attached on top of test piece 1. Next, a 1 kg rubber roll was rolled twice back and forth at a speed of 600 mm / min on the test piece 2, leaving the edge. The sample after the pressure bonding (a sample having a laminated structure of Bakelite plate-test piece 1-test piece 2) was immersed in water at 45° C. for 30 minutes. After 30 minutes, the sample was taken out of the water and the moisture on the sample surface was lightly wiped off. Using an Instron tensile tester, test piece 2 was peeled off from test piece 1 at a peel angle of 180 degrees and a peel speed of 300 mm / min, and the 180° peel strength (self-backside adhesive strength, unit: N / 15 mm) of test piece 2 against test piece 1 was measured (average value of N=3). The measurement atmosphere was a temperature of 23±2°C and a relative humidity of 50±5%.
[0037] [Tensile test: 20% tensile load] For the patches (without a patch) of Examples 1 to 4 and Comparative Examples 1 and 2, a 20% tensile load was measured in accordance with JIS L 1096 using an Instron tensile tester. The patch of each example was cut to 200 mm in the longitudinal direction of the support (knitted fabric) × 20 mm in the transverse direction, and the release material was peeled off to obtain a test piece. The tensile load was measured at a chuck distance of 100 mm and a moving speed of 300 mm / min. The tensile load value (unit: N / 20 mm) was measured when the moving distance reached 20% (average value of N=5). The measurement atmosphere was a temperature of 23±2°C and a relative humidity of 50±5%.
[0038] [Moisture permeability] For the patches of Examples 1 to 4 and Comparative Examples 1 and 2 (without a patch and with the release liner removed), moisture permeability was measured under measurement conditions of a temperature of 40° C. and a relative humidity of 90% in accordance with JIS Z 0208 (calcium chloride method).
[0039] [Practical test: rag wringing test] A water-soaked cloth was wrung out between the fingers to which each example patch (with pad) had been applied, and the adhesion of the patch at that time was evaluated according to the following procedure. Placement position - Place the pad on the back of your hand and wrap it around the second joint of your fingers (index finger, middle finger, ring finger). - Place the pad on the fingertips (index finger, middle finger, ring finger) so that it is wrapped around the fingertips. Test procedure Each test sample patch was applied to the application site (second joint of the finger, fingertip) when it was dry, and 30 minutes after application, the patch was wrung out using a rag soaked in detergent water [0.75 mL of household dishwashing detergent (product name "Kyukyutto Clear Disinfectant", Kao Corporation) dissolved in 1 mL of water (manufacturer's recommended concentration)]. One set consisted of wringing out the cloth once and bending and straightening the fingers three times, and after ten sets, the state of application (attachment) of the sample was evaluated according to the evaluation criteria (see below). In order to evaluate the deviation of the application position, marks were made on the top and bottom of the tape application position on the pad side when it was applied. The test was conducted by three subjects for each sample (N=3), and an average score of 4.0 or higher was marked as O, 2.1 to 3.9 as △, and 2.0 or less as × (average scores were rounded to one decimal place). <Evaluation Criteria (1): Adhesion to Skin> 5. Fully attached 4. Edges are slightly peeled off About 3 1 / 3 peeled off 2. About half of it peeled off 1. The pad has peeled off so much that it can be turned over. 0 falling off <Evaluation criterion (2): Adhesion of overlapping parts> 5. Fully attached 4. Edges are slightly peeled off About 3 1 / 3 peeled off 2. About half of it peeled off About 1 2 / 3 peeled off 0 All overlapping parts peeled off
[0040] [Table 1]
[0041] As shown in Table 1, in the adhesive materials of Examples 1 to 4, which have a post-immersion adhesive strength of 2.0 N / 15 mm or more, the mesh fabric backing has a course density of more than 210 threads / inch and less than 270 threads / inch, the thickness of the backing is 0.24 mm to 0.40 mm, and the 20% tensile load is The strength was 2.5N / 20mm to 4.5N / mm, and when the patch was actually applied to the fingers and subjected to a dust cloth wringing test simulating wet work, it was confirmed that the patch had excellent adhesion to the skin and adhesion to the overlapping area. Furthermore, after the test, no adhesive residue was found on the fingers after the patch was peeled off, confirming that the patch did not leave any adhesive residue. On the other hand, the patch of Comparative Example 1, in which the adhesive strength of its own backside after immersion was significantly lower than 2.0 N / 15 mm (0.68 N / 15 mm), and the mesh fabric backing had a course density of 56 threads / inch and a thickness of 0.46 mm, had a 20% tensile load of 3.6 N / 20 mm, but its adhesion to the skin was rated as △ (score: 2.1 to 3.9), and the adhesion of the overlapping area was rated as × (score: 2.0 or less). Furthermore, after immersion, the adhesive strength of the backing was below 2.0 N / 15 mm, and although the course density of the mesh fabric backing was 210 threads / inch or less, the patch of Comparative Example 2, in which the backing was 0.38 mm thick, had a high 20% tensile load of 5.0 N / 20 mm, and adhesion to the skin was rated as × (score: 2.0 or less), and the adhesion of the overlapping area was also rated as △ (score: 2.1 to 3.9). As shown by the results of the Examples above, the patch of the present invention has high adhesive strength on its back side even after immersion in water, and therefore, even after practical tests simulating work involving washing with water, it was confirmed to be a patch with excellent adhesion, in which peeling not only from the skin but also from the overlapping areas was suppressed, and no glue was left behind.
Claims
1. A patch having a support and a pressure-sensitive adhesive layer provided on one side of the support, The adhesive layer of the adhesive material is attached to the surface of the support of the adhesive material, which is then immersed in water at 45°C for 30 minutes. In a post-immersion backside adhesive strength test in which the adhesive strength is measured after removal from the water, the post-immersion backside adhesive strength (longitudinal direction) is 2.0 N / 15 mm or more.
2. The support is a knitted fabric made of polyester non-elastic yarn and polyurethane elastic yarn, The knitted fabric comprises: The course density is more than 210 fibers / inch and not more than 270 fibers / inch; The thickness is 0.25 mm to 0.40 mm. The patch according to claim 1.
3. The knitted fabric comprises: The well density is 25 wells / inch to 50 wells / inch; The polyester non-elastic yarn has a fineness of 30 to 100 dtex; The polyurethane elastic yarn has a fineness of 100 to 300 dtex; Weight per unit area: 80g / m 2 ~150g / m 2 That is, The patch according to claim 2.
4. The adhesive material has a 20% tensile load in its longitudinal direction of 2.5 N / 20 mm to 4.5 N / 20 mm. The patch according to claim 1.
5. The adhesive has a moisture permeability of 3,000 g / m 2 ・24 hours or more, The patch according to claim 1.
6. The adhesive material according to claim 1 , wherein the adhesive layer comprises a foamed acrylic adhesive.
7. The adhesive material according to claim 1, which does not leave any adhesive residue.
Citation Information
Patent Citations
Fabric for tape, skin adhesive tape using the same, and method for producing the fabric for tape
JP2011032625A
Applying material
JP2011067615A